SAT0359 Evaluation of Medication Compliance in behÇet's Disease. (15th July 2016) - Cinar, M.; Cinar, F.I.; Yilmaz, S.; Acikel, C.; Cakar, M.; Simsek, I.
Abstract : Background: The management of Behcet's disease (BD) should be tailored to each patient by taking into account the existing symptoms, clinical manifestations and prognostic factors. Since there are effective treatment alternatives for each manifestation, the patient's adherence to treatment is one of the most important elements for a successful management of the disease. Adherence to treatment in patients with BD is not known well Objectives: To investigate the compliance status to drug therapy in patients with BD. Methods: This study was conducted at the rheumatology outpatient clinic of a tertiary hospital and 125 BD patients were included. Patient interview form, the Turkish Translation of the Compliance Questionnaire on Rheumatology (2015) (CQR-T; score 0–100), validated by Cinar et al, and Morisky Medication Adherence Scale, developed by Morisky (1986), were used to determine the sociodemographic and medical characteristics. In addition, disease activity was evaluated with Behcet's Syndrome Activity Score (BSAS, score =0–100) and Behcet's Disease Current Activity Form (BDCAF; score =0–12). Results: The mean age of the patients was 31.42 ± 8.11 years and 91.2% were male. The mean disease duration, age at diagnosis, BDCAF score and BSAS score of patients were 9.34 ± 5.76 years, 25.02 ± 7.82 years, 4.79 ± 2.05 and 45.22 ± 23.56, respectively. 76.8% of the patients were using colchicine, 44.8% azathioprine, 16.0% corticosteroids, 4.8% cyclosporine, 4.0% cyclophosphamide, 4.0% infliximab, 3.2% non-steroidal anti-inflammatory drugs, 2.4% methotrexate, 1.6% sulfasalazine and 7.2% were using anticoagulants. 40 patients (32.0%) experienced drug-induced side effects. The total CQR-T score of patients was 66.48 ± 13.49 (min: 19.30-max: 94.74). According to the Morisky Medication Adherence Scale, medication compliance score of the patients was high in 25.6%, medium in 55.2%, and lower in 19.22% of patients. The total Morisky Medication Adherence Scale score was 1.43 ± 1.16 (min-max, 0–4). The demographic/medical characteristics of the patients (age, sex, marital status, education level, employment status, social support status, treatment, transportation, disease duration, symptom onset time, BSAS, BDCAF, ESR and CRP) had no association with total CQR-T scores. The total CQR-T score had a significant but weak correlation (r =0.197; p=0.027) with the age at diagnosis. Conclusions: In our study, it was found that the majority of treated patients were at an intermediate level of compliance status. Adherence to treatment status of patients increases with increasing ages at diagnosis. This study emphasizes the necessity of developing new strategies for increasing the patients' adherence. References: Morisky DE, Green LW, Levine DM. Concurrent and predictive validity of a self-reported measure of medication adherence. Med Care. 1986 Jan;24(1):67–74. Cinar FI, Cinar M, Yilmaz S, Acikel C, Erdem H, Pay S, Simsek I. Cross-Cultural Adaptation, Reliability, and Validity of the Turkish Version of the Compliance Questionnaire on Rheumatology in Patients With Behçet's Disease. J Transcult Nurs. 2015 Mar 22. pii: 1043659615577699. Disclosure of Interest: None declared